Work engagement interventions can be effective: A systematic review - Knight, Caroline; Patterson, Malcolm; Dawson, Jeremy (2019)
Purpose: To synthesise work engagement intervention studies and inform future research by exploring: (1) the types, styles and content of engagement interventions; (2) their effectiveness; and (3) their underlying mechanisms.